PEMANFAATAN TEPUNG KIJING (Pilsbryoconcha sp.) SEBAGAI SUBSTITUSI TEPUNG IKAN DALAM FORMULASI PAKAN IKAN PATIN SIAM (Pangasius hypopthalmus) - Gideon WDP; Yulisman .; Ade Dwi Sasanti (Jurnal Akuakultur Rawa Indonesia, 2014)
ABSTRACT This aims of this research were to determine the percentage of clam meal in substitute fish meal in feed formulations seen from the value of digestibility, growth and feed efficiency. This study was conducted in July-September 2013 in the Laboratory of Aquaculture, Aquaculture Program, Faculty of Agriculture, Sriwijaya University, Cr2O3 and proximate analysis test conducted in Bioprocess Laboratory, Department of Chemical Engineering, University of Sriwijaya. The design used was a completely randomized design, using five treatments with three replications. The treatment used is flour substitution of fish meal with a clam on which treatment A (0:100), B (25:75), C (50:50), D (75:25), and E (0:100). In the observed parameters of feed digestibility, growth, feed efficiency, survival, and quality of water. Results showed treatment B (clam meal 25% and 75% fish meal in feed formulation) resulted in a total value of digestibility, protein digestibility of feed, growth and feed efficiency is highest, where the value was 89.51%, 93.23%, 2.07g, 85.72%. Keywords: Clam, feed digestibility, growth, feed efficiency, catfish.